Korelasi IRMS dan BMS Terhadap Tingkat Pelayanan Ruas Jalan Nasional - Yohanes Martono Hadi (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2012)
The road is expected to meet the criteria of "Fast, Nyama, Safe, Beautiful and Sustainable" ascriteria for reviewing the performance of roads. Evaluation or study was conducted to review oneaspect of road based on speed or travel time required by the traffic on the roads, and theevaluation is done by correlating the data IRMS (Integrated Roads Management System) and BMS(Bridges Management System) to services section one way to road performance component of"travel time" traffic required for condition of roads and bridges on the road conditions, theprimary and secondary data conducted in 2010 on the national road network in the province ofJambi using data IRMS in 2010 and BMS in 2009. This study aims to review the performance ofthe street on the national road network in the province of Jambi. Thus it can be taken a linkagethat the travel time required by the traffic to move from one place to another are affected by thecondition of roads and bridges on the road, up to now the results of the IRMS and BMS as aninstrument (Benchmark / Standard) used by policy makers as a basis for determining future goodprogram planning, maintenance, and development. While the actual conditions on the ground arenot in accordance with the results of the IRMS and BMS were taken by decision of the currentconditions specified policy.